Disability in the history of art and anti-ableism of contemporary art - Stawowy, Joanna (Understanding Disability: Issues, Research, Reflections, 2021)
The subject of illness and disability has been explored by artists for a long time. Depending on the era, it was presented in different ways. Twentieth-century social movements, interested in emancipating otherness, shed new light on the perception of the human body and its causative capabilities. Currently, the artist is more a commentator of reality than its passive observer and disability is one of the most important subjects of art. The exclusion, which used to involve disabled people, seems to be passing nowadays, however the problem of ableism still exists. Contemporary artists refer to it in their works trying to face harmful stereotypes. The purpose of this article is to look at disability through the eyes of artists, to find its representations in works of art and to trace how the perception of the disabled body has changed, based on the aesthetics and canon of a given age – from the perfect body of antique to the social involvement of contemporary art.